Enhancing the Jacobi method with the CBFM for array antenna analysis - Ludick, D.; Botha, M.; Davidson, David; Maaskant, R. (2017)
© 2017 IEEE. The analysis of sparse, disjoint finite antenna array structures is considered in this work. The Method-of-Moments (MoM) based CBFM-enhanced Jacobi technique is presented, and offers an improvement over the standard iterative Jacobi method in terms of convergence and accuracy. By applying the Characteristic Basis Function Method (CBFM) during each iteration the effect of mutual coupling between the array elements can be accounted for more accurately than in the standard Jacobi method. The convergence rate of the method is found to be better than that of the Jacobi technique.